HISTORIOGRAPHY OF THE STUDY OF THE UKRAINIAN GREEK CATHOLIC CHURCH IN WESTERN UKRAINE IN THE EARLY STAGES OF THE UNDERGROUND (Південний архів (історичні науки), 2025)
The article aims to perform a comprehensive historiographical analysis of the research into the early underground activities of the Ukrainian Greek Catholic Church (UGCC) in Western Ukraine. We seek to trace the evolution of approaches to this issue in different historical and ideological contexts and identify the main narratives and conceptual frameworks within which the UGCC’s activities were interpreted. The methodology of our study is based on the interdisciplinary approach that combines historiographical analysis, the theories of historical and cultural memory, postcolonial studies, and discourse analysis. We also employed the approaches from everyday history to gain a deeper understanding of the life dimension of underground religious practices. The article’s main content includes a systemic review of the primary stages in the development of historiography on the UGCC in underground conditions.We analyzed the Soviet historiography from the 1940s to the 1980s, which presented the UGCC as an “anti-Soviet element” and “the Vatican’s agent” through an ideological lens, denying the fact of religious persecutions and interpreting the violent liquidation of the Church as a “voluntary reunification with Orthodoxy”. The diaspora historiography from the 1940s to the 1980s presents the UGCC as a spiritual resistance to totalitarianism and considers its persecution an act of genocide against Ukrainians’ religious life, highlighting the preservation of church and national identities. The post-Soviet Ukrainian historiography from the 1990s to the 2000s, due to the introduction of archival sources from the SSU, MIA, and CSAPUU into scientific circulation, reinterpreted the events and, for the first time, objectively presented the mechanisms of the violent liquidation of the UGCC, the underground activities of the episcopate and clergy. The western scientific historiography analyzes the UGCC as an example of the religious resistance to the totalitarian system, including it in the broader context of the USSR’s repressive policies towards religious institutions and the research into religious freedom in Central and Eastern Europe. The conclusions emphasize that the historiography of the UGCC’s underground activities evolved from rigid ideological Soviet interpretations to contemporary multi-level interpretations considering political, cultural, and spiritual aspects of the Church’s resistance to the Soviet repressive system. We underscore the importance of further interdisciplinary studies, which will allow for a deeper understanding of the phenomenon of the Church’s underground existence as a component of Ukrainian historical memory and national identity.
Keywords: Ukrainian Greek Catholic Church, historiography, Soviet policy, totalitarian system, religious persecutions, underground, historical memory